Entanglement and physical attributes of the interaction between two SC-qubits and thermal field in the presence of a magnetic field. (April 2019) - Al Naim, Abdullah F.; Khan, Javed Y.; Abdel-Khalek, S.; Khalil, E.M.
Abstract: The interaction between two superconducting (SC) qubits and thermal field in the presence of a magnetic field, the qubit–qubit interaction and the Stark interaction are investigated. The wave function, and hence density matrix, that describe this system is obtained and the behavior of physical quantities that characterize it are evaluated. In particular, the von Neumann entropy and quantum concurrence as a measure of entanglement between parts of the system are discussed in detail. The effects of thermal and low temperature on the dynamical properties of the von Neumann entropy and nonclassical correlation are discussed. Also, the influences of the atomic coherence and magnetic field on the statistical properties of the physical quantities are examined. Moreover, some important physical phenomena during the time evolution of the interaction between the two SC-qubits, thermal field, and magnetic field are explored. The nonclassical correlation between the thermal field and the two SC-qubits is enhanced by increasing temperature whereas the SC qubit–qubit entanglement decreases. The magnetic field and Stark shifts play a central role in the dynamical and physical attributes of the two types of entanglement. Highlights: The interaction between two SC-qubits and thermal field in the presence of magnetic field. The general solution in non-resonance case is obtained. The entanglement between the two subsystems is discussed. Finding the relation between the classical external field and the degree of entanglement.